Understanding China’s Geoeconomic Maneuver Against Ethiopia Through an Energy Geopolitical Perspective - Dionius Christopher, Aurel (Journal of International Relations on Energy Affairs, 2022)
Departing from the need for energy supply which increases every year, China's foreign policy through the Belt Road Initiative (BRI) is trying to maneuver against areas in the world, including Africa. The African region is one of the regions in that China has given various kinds of assistance to trigger economic growth for countries in the region. Where one of the countries that China is aiming for is Ethiopia as a landlocked country, this research will provide an analytical description of China's interests in geoeconomic maneuvering against Ethiopia through the perspective of energy geopolitics. This study uses descriptive qualitative research methods in data collection, the material of which is sourced from the existing literature. Research on China's geoeconomic maneuvers against Ethiopia shows that China needs Ethiopia as an access point for energy transportation to be channeled to the State of Djibouti, where the country has one of the largest ports in the world and is strategically located in the world's trade routes.